(untitled) (AYUSHDHARA, 2015)
DMD is one among the most common muscular disorders. The incidence is 1:3600 live born infant boys worldwide. It is X-linked recessive disease caused by a deficiency of a normal muscle protein called dystrophin, which maintains the integrity of the muscle cell wall. Eventually irreversible progressive muscle weakness and degeneration of the skeletal or voluntary muscles, which control movement leading to lose the ability to stand, walk and loss of ambulation before 10years, with progression of the disease, most patients succumb to death in their early 20s. As there is no specific treatment in any system of medicine and the disease prognosis is unpreventable but if we start treatment in early stages of ambulant DMD boys, it may slow or stop the progressive degeneration of muscles. DMD cannot be directly co-related with any single disease in Ayurveda. All most all major neuromuscular disorders are identified with Vata dosha. In Ayurveda this pathogenesis can be clearly understood by the concept of Adhi bala pravritta vyadhi. Here the pathogenesis occurs due to the Beeja bhagavayava dusti which leads to Mamsa vata dushti. The present study was under taken to increase functional and physical capabilities, minimizing disability to delay further progression of disease and to maintain the ambulation for longer time and to improve quality in the activities of daily living. 30 children with DMD were taken up for the study of age between 05-16years and were given treatment for 2 weeks consisting of Abhyanga with Bala taila, shastika shali Pinda swedana followed by Vasti. The study has been subjected to statistical analysis, in which the results were found to be encouraging.